Health Status and Labour Force Status of Older Working-Age Australian Men - Kalb, G; Cai, L (My University, 2005)
The trend of declining labour force participation by older working-age men, combined with an ageing population, has led many industrialised nations to develop policies encouraging older male workers to remain in the labour force. A better understanding of how an individual’s health influences the labour force participation decision among this group of workers would facilitate the development of effective policies. The current research uses the Household, Income and Labour Dynamics in Australia (HILDA) survey to investigate the issue. The longitudinal nature of the three-wave HILDA data, which are currently available, allows for a better control for unobserved heterogeneity than was possible with earlier data. Therefore, more efficient estimates of the direct health effects on labour force participation can be obtained than in a cross-sectional analysis. Unobserved factors are likely to affect both health and labour force status, therefore we estimate a model that takes the correlation between the two error terms in the health and labour force status equations into account. The results show that controlling for unobserved heterogeneity and the correlation between the two equations is important. That is, the estimated variances of the unobserved heterogeneity terms are significantly different from zero in both equations and the two error terms are correlated. Any restriction on the correlation between the two equations appears to lead to underestimation of the direct health effects.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Gender -- Male; Gender; Employment; Employment -- Labour force status and attachment; Health; Health and wellbeing; Labour market; Health; Employment and unemployment